2017
DOI: 10.1590/abd1806-4841.20175794
|View full text |Cite
|
Sign up to set email alerts
|

Final diagnosis of 86 cases included in differential diagnosis of American tegumentary leishmaniasis in a Brazilian sample: a retrospective cross-sectional study

Abstract: BackgroundCutaneous leishmaniasis is distributed worldwide, including Brazil. Its several clinical forms need to be distinguished from other dermatoses. Clinical similarities and lack of a gold standard diagnostic tool make leishmaniasis-like lesions a challenging diagnosis.Objectives.To report the final diagnosis of patients primarily suspected of having American tegumentary leishmaniasis (ATL).Methods.A retrospective cross-sectional study was conducted on the basis of medical records of 437 patients with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…The injury in mucosa may result in sequelae due to fibrosis, leading to anatomic and functional alterations in the affected sites [ 4 , 8 ]. A study performed in Brazil indicated that paracoccidioidomycosis was the main differential diagnosis of infectious etiology for leishmaniasis [ 9 ]. Therefore, the establishment of a correct and timely diagnosis is essential to avoid complications in both diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The injury in mucosa may result in sequelae due to fibrosis, leading to anatomic and functional alterations in the affected sites [ 4 , 8 ]. A study performed in Brazil indicated that paracoccidioidomycosis was the main differential diagnosis of infectious etiology for leishmaniasis [ 9 ]. Therefore, the establishment of a correct and timely diagnosis is essential to avoid complications in both diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The same can occur with cases of VL and Leprosy [60] and with the adoption of IFR and cytometry. Thus, it is essential that specific antigens be developed and that, in the case of application of these tests in clinical practice, a differential diagnosis be made [7]. In relation to cytometry, although the technique has also shown high sensitivity and specificity and presents advantages over other enzyme immunoassays [61], it is costly and requires specialised technicians to perform the cytofluorometric method.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding smear slide and histopathology, their low sensitivity values can be attributed to lesion chronicity, in which macrophages tend to reduce their load or disappear. Moreover, there may also be an observation bias in the examiner of the material to be analysed [7,62]. The direct examination technique is widely used by the Brazilian public health service because of its low cost and for being widely available in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health managers should pay special attention to professionals inability in performing CL diagnostic exams, especially in the primary health care centers 20 . The differential diagnosis of CL are still challenging for physicians because of the wide number of dermatological diseases with similar clinical manifestations 21 and the lack of access to material and technical resources (including the Montenegro test, surgical material, and resources for biopsy and parasitological examination). Moreover, the scarcity of electrocardiogram and laboratory equipment to perform the necessary tests for monitoring toxicity hampers patients' treatment near their home.…”
Section: Discussionmentioning
confidence: 99%